2008
DOI: 10.1007/s10265-008-0149-9
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent growth and emergence of functional leaves: an adaptive mechanism in the seedlings of the western Himalayan plant Podophyllum hexandrum

Abstract: As an adaptive mechanism, hypocotyl dormancy delays emergence of functional leaf until favorable season of growth in Podophyllum hexandrum, an endangered medicinal plant of the western Himalayas. However, upon exposure of the freshly germinated seedlings to favorable temperature (25 degrees C), functional leaves emerged within 20 days. Therefore, we examined regulation mechanisms of growth and development of this alpine plant by temperature under laboratory conditions. The seedlings were exposed to (1) 25 degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 14 publications
(14 reference statements)
0
11
0
Order By: Relevance
“…Hence, most alpine plants exhibit opportunistic growth behavior not only to complete their time-bound growth targets, but also to store ample reserves of primary metabolites much before the onset of harsh winters. Since P. hexandrum also exhibits such behavior, it attains maximum vegetative growth during the summers, the time when the growth-favoring environmental temperature (i.e., about 25°C) prevails [6]. Even under the milder temperate climate of Palampur where a favorable temperature regime prevails for longer duration, P. hexandrum exhibits this behavior.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Hence, most alpine plants exhibit opportunistic growth behavior not only to complete their time-bound growth targets, but also to store ample reserves of primary metabolites much before the onset of harsh winters. Since P. hexandrum also exhibits such behavior, it attains maximum vegetative growth during the summers, the time when the growth-favoring environmental temperature (i.e., about 25°C) prevails [6]. Even under the milder temperate climate of Palampur where a favorable temperature regime prevails for longer duration, P. hexandrum exhibits this behavior.…”
Section: Discussionmentioning
confidence: 91%
“…2b-g, 3). Earlier, Kushwaha et al [6] showed that senescence of aerial green photosynthetic parts was initiated at temperatures below 15°C, and metabolites were mobilized to the below-ground parts. This enabled the plants to survive the low winter temperatures (4°C or lower) under in situ conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Like other alpine plant species [ 6 ], S. hexandrum has been reported to be sensitive to high temperature [ 7 ]. S. hexandrum consumed more starch at 25°C as compared to at 10°C leading to poor root growth at the former temperature [ 7 ]. Also, the rate of photosynthesis was reported to be lower at 30°C as compared to at 20°C.…”
Section: Introductionmentioning
confidence: 99%
“…To this, 10 ml de-ionized water was added along with ammonia solution (1:1) until a yellow colour developed. Absorbance was read at 420 nm and the level of nitrate determined using spectrophotometer (Hitachi, Japan) against a standard curve prepared with KNO 3 (Kushwaha et al 2008).…”
Section: Effect Of Betaine On Nutrient Absorptionmentioning
confidence: 99%